Integration of Project-Based STEM Learning in the Meliuk Menerjang Material within the Emancipated Curriculum - Mardhatillah; Shirly Rizki Kusumaningrum; Ade Eka Anggraini; Siti Faizah; Muhammad Aidi Noor Ihsan; Lili Kasmini (Postgraduate, University of Mataram, 2024)
This study aims to develop a project-based STEM (Science, Technology, Engineering, and Mathematics) learning tool for the